How Youtube Assist Teachers in Developing Material? - Ray, Laila Maryam; Satri, Rara; Uswatunisa, Sofia; Harahap, Syarifah Aini (Education and Talent Development Center Indonesia (ETDC Indonesia), 2021)
In a technology revolution period which all of the activities of humans also relate to the use of all of the technologies. Thus, using technology hopefully will help them to make easier in their works. However, in the educational world, it is also needed by the teacher to make the teacher or students easy during the teaching and learning process. The purpose of this paper aid how technology can help teachers during the teaching and learning process especially by using YouTube. The methodology used in this paper is by using a literature review from several journal articles that related to how YouTube assists the teacher in developing material during the teaching and learning process that is appropriate for foreign language context.